Pharmacokinetics of a liposomal formulation of doxorubicin in rats - Zongyu Liu; Ye Bi; Yating Sun; Fei Hao; Jiahui Lu; Qingfan Meng; Robert J. Lee; Yaping Tian; Jing Xie (Elsevier, 2017)
Background: Measuring free drug concentration following systemic administration of a liposomal drug is a crucial aspect of the assessment of its in vivo behavior. Therefore we require an efficient method to separate free drug in the plasma from encapsulated drug. Objectives: To study the pharmacokinetics of free doxorubicin (DOX) released from liposomal doxorubicin (L-DOX) in rats. Methods: L-DOX was prepared with encapsulation efficiency of 90% and was injected intravenously into rats. A solid-phase extraction (SPE) method coupled with UPLC-MS/MS was used to measure the concentration of F-DOX in rat plasma without disrupting the integrity of L-DOX. Results: This method exhibited a linear range of F-DOX from 0.2 to 200 ng/mL. Recovery, precision, linearity and accuracy of this technique appear satisfactory for pharmacokinetic study. The constituents of F-DOX ranged from 5.35% to 14.09% of total DOX in plasma at each time point measured after L-DOX administration. Conclusion: SPE method was suitable for studying the pharmacokinetics of F-DOX in rats receiving L-DOX. Keywords: Pharmacokinetics, Doxorubicin, Liposomes, Solid-phase extraction